Peran Pembinaan Kerohanian dalam Kesehatan Mental Narapidana di Lembaga Pemasyarakatan Kelas II A Kerobokan: Penelitian - I Komang Wira Dharma Sentana; Denny Nazaria Rifani (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This study aims to determine: The Role of Spiritual Guidance on the Mental Health of Inmates at Class II A Kerobokan Penitentiary. The research method used is a qualitative descriptive approach research method including: (1) The location of the study is located at Class II A Kerobokan Penitentiary. (2) The technique of determining informants by determining key informants, from key informants then the researcher develops further to find informants for assistance. (3) The data collection technique uses three techniques, namely: observation techniques, interview techniques, and document study techniques. (4) Data analysis techniques consisting of data collection, data reduction, data presentation, verification. The results of this study are that inmates are helped by the existence of spiritual guidance in the mental health of inmates at Class II A Kerobokan Penitentiary, although there are several obstacles but in general the program runs smoothly and effectively.